2016
DOI: 10.1093/femsec/fiw004
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic analysis of the microbial community in stored sugar beets using high-throughput sequencing of different marker genes

Abstract: Post-harvest colonization of sugar beets accompanied by rot development is a serious problem due to sugar losses and negative impact on processing quality. Studies on the microbial community associated with rot development and factors shaping their structure are missing. Therefore, high-throughput sequencing was applied to describe the influence of environment, plant genotype and storage temperature (8°C and 20°C) on three different communities in stored sugar beets, namely fungi (internal transcribed spacers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 65 publications
2
37
0
Order By: Relevance
“…On stored sugar beet roots, P. vulpinum has been shown to be the most prevalent Penicillium species in older literature, while other Penicillium species have also been documented to occur: P. cyclopium, P. duclauxii, P. expansum, P. funiculosum [now T. funiculosus], P. paneum, P. rubrum, P. stoloniferum, and P. variable [now T. variabilis] (Bugbee 1975, Bugbee and Nielsen 1978, Fugate and Campbell 2009, Liebe et al 2016, Morotchkovsky 1936, Samson et al 2011, Visagie et al 2014. In a recent fungicide study (Strausbaugh et al 2015) in a Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On stored sugar beet roots, P. vulpinum has been shown to be the most prevalent Penicillium species in older literature, while other Penicillium species have also been documented to occur: P. cyclopium, P. duclauxii, P. expansum, P. funiculosum [now T. funiculosus], P. paneum, P. rubrum, P. stoloniferum, and P. variable [now T. variabilis] (Bugbee 1975, Bugbee and Nielsen 1978, Fugate and Campbell 2009, Liebe et al 2016, Morotchkovsky 1936, Samson et al 2011, Visagie et al 2014. In a recent fungicide study (Strausbaugh et al 2015) in a Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Penicillium species involved in storage rot have frequently been associated with wounds and are prevalent, but not necessarily the most damaging pathogen present (Bugbee 1975(Bugbee , 1982(Bugbee , 1993Nielsen 1978, Fugate andCampbell 2009;Liebe et al 2016;Mumford and Wyse 1976). In the 1970s in the Red River Valley, P. vulpinum and Phoma betae were isolated more than 70% of the time, but P. betae was considered the more damaging pathogen because it decayed roots at a faster rate (Bugbee 1982).…”
Section: Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Liebe et al . (2016) reported shifts in the fungal and oomycete community composition associated with storage soft rot development in different sugar beet hybrids from different environments stored at different temperatures. Interestingly, while the genotypes showed differences in the susceptibility to soft rot, the shifts in the microbial community of sugar beet were genotype independent.…”
mentioning
confidence: 99%
“…Interestingly, while the genotypes showed differences in the susceptibility to soft rot, the shifts in the microbial community of sugar beet were genotype independent. The authors suggested an unspecific resistance mechanism slowing down the spread of pathogens in more resistant genotypes but not preventing infection (Liebe et al ., 2016). However, the study focused on fungi and oomycetes and the dynamics of bacteria community during storage soft rot development of sugar beet and its putative role in disease expression remains elusive.…”
mentioning
confidence: 99%